ANALISIS KEPUASAN PEMEGANG POLIS ATAS PELAYANAN PT. PRUDENTIAL LIFE ASSURANCE SM1 SEMARANG - Ruditya Endi Pratama; Hari Susanta Nugraha; Sendhang Nurseto (Universitas Diponegoro, 2012)
The purpose of this study is to examine the satisfaction of insurance police holder of PT. Prudential Life SM1 Semarang upon service rendered to insurance police holder. This study uses the type of descriptive research. The results of this research is satisfaction of customer based on dimension of quality of responsiveness, reliability, assurance, empathy and direct evidence which is nearly in accordance with customers expectation. Result of analysis shows that accordance between expectation and performance of the quick and proper service about the process of police issuance was 87.45%. The process of police cashing was 90.11%, administration procedure and easy payment was 85.27%, providing clear and easy-to-understand information was 84.05%, responsiveness of PT. Prudential Life SM1 Semarang’s employee was 88.25%, capability of employee to respond to complaint and problem of customers was 83.30%, answering telephone from customer well and quickly was 80.19%, accuracy of information related to claims was 83.55%, employee’s knowledge and skill was 85.78%, polite and friendly service were 89.89%, employee’s integrity was 87.44%, assurance of security and trust against customers was 82.53%. Generally, result of analysis shows that service of PT. Prudential Life SM1 Semarang toward insurance police holder was satisfactory enough.